Experimental and simulative investigations on a phase change material nano-emulsion-based liquid cooling thermal management system for a lithium-ion battery pack. (15th September 2020) - Wang, Fangxian; Cao, Jiahao; Ling, Ziye; Zhang, Zhengguo; Fang, Xiaoming
Abstract: Thermal management systems (TMSs) are indispensable for practical applications of lithium-ion battery packs. In this study, phase change material (PCM) nano-emulsions with enhanced energy storage capacity, excellent dispersion stability, low viscosity and good thermal reliability were employed as coolants for high-performance liquid cooling thermal management systems (LCTMSs) for the first time. The maximum temperature ( T max ) and maximum temperature difference ( Δ T max ) in a 5S4P battery pack were measured to evaluate the thermal management performance of these coolants. When a 10 wt% OP28E nano-emulsion was used at a flow rate of 200 mL min −1, T max and Δ T max were 1.1 °C and 0.8 °C, respectively, lower than those based on water, at a discharge rate of 2C. The increase in OP28E mass fraction of the nano-emulsion led to a gradual decrease in T max and Δ T max at identical discharge rates. Simulation studies were also conducted and validated by comparing with the experimental results. It was revealed that, T max and Δ T max decreased with increasing flow rate of the coolants, and the thermal management performance of the 10 wt% OP28E nano-emulsion was always better than that of water. This work sheds light on improving the performance of LCTMSs by using PCM nano-emulsions. Graphical abstract: Image 1 Highlights: The OP28E nano-emulsion had enhanced energy storage capacity and low viscosity. PCM nano-emulsion was employed as a novel coolant for a LCTMS. T max and Δ T max of battery pack decreased with increasing OP28E concentration. LCTMS performance based on 10 wt% OP28E nano-emulsion was better than that of water.